Open Resection (OR) versus Laparoscopic Assisted Resection (LAR) in patients with colorectal cancer at Hospital Taiping retrospective study - Pillai, Mohanasundram (2010)
Colorectal carcinoma is one of the common malignant neoplasm in this country. Minimally invasive surgery in colorectal cancer patients has improved quality of life; however the impact of this development has not been studied in this population. To study the epidemiology of colorectal carcinoma in the Larut, Matang and Selama district. The primary objective was to evaluate short term benefits of laparoscopic assisted resection in colorectal malignancy and the feasibility of undertaking this at a district hospital. Between January 2005 to December 2009, all patients diagnosed with colorectal malignancy requiring surgery were included in this study. The sex, age, and ethnicity were reviewed as part of epidemiology study. Type of surgery, duration of surgery, duration of stay post op and surgical free margin were compared between laparoscopic assisted resection (LAR) group and open resection (OR) group. All these data’s were traced from the operative notes, patient notes and histopathological report. 193 patients were studied for 5 years period ranging from January 2005 till December 2009. The ratio of patients underwent OR compared to LAR was 2: 1. There was almost equal sex distribution in each group. Majority of patients are Malay .The average age at presentation was 62 in OR and 58 in LAR group. There is no statistically significant difference in duration of operation between LAR and OR method of surgery. The length of hospital stay post op in LAR group is significantly shorter compared OR (p <0.05) The post op morbidity and surgical free margin has no significant association between methods of surgery. Laparoscopic assisted surgery for colorectal cancer is as effective and safe as conventional surgery in the short term.